Chinese Wheat Mosaic Virus-Induced Gene Silencing in Monocots and Dicots at Low Temperature - Yang, Jian; Zhang, Tian-Ye; Liao, Qian-Sheng; He, Long; Li, Juang; Zhang, Heng-Mu; Chen, Xuan; Li, Jing; Yang, Jin; Li, Jin-Bang; Chen, Jian-Ping (Frontiers in Plant Science, 2018)
Virus induced gene silencing (VIGS) is an important tool for functional genomics studies in plants. With this method, it is possible to target most endogenous genes and down-regulate the messenger RNA (mRNA) in a sequence-specific manner. Chinese wheat mosaic virus (CWMV) has a bipartite, single-strand positive RNA genome and can infect both wheat and N. benthamiana, and the optimal temperature for systemic infection in plants is 17℃. To assess the potential of the virus as a vector for gene silencing at low temperature, a fragment of the N. benthamiana or wheat phytoene desaturase (PDS) gene was expressed from a modified CWMV RNA2 clone and the resulting photo bleaching in infected plants was used as a reporter for silencing. Down-regulation of PDS mRNA was also measured by quantitative reverse-transcriptase polymerase chain reaction (RT-qPCR). In experiments using fragments of PDS ranging from 500 to 1500 nucleotides, insert length influenced the stability and the efficiency of VIGS. The CWMV induced silencing system was also used to suppress miR165/166 and miR3134a through expression of miRNA target mimics. The relative expression levels of mature miR165/166 and miR3134a decreased whereas the transcript levels of their target genes increased. Interestingly, we also found the CWMV induced silencing system was more efficient compare with the vector based on Barley stripe mosaic virus (BSMV) or Foxtail mosaic virus (FoMV) in wheat or the vector based on TRV in N. benthamiana at 17 ℃. In summary, the CWMV vector is effective in silencing endogenous genes and miRNAs at 17 ℃, thereby providing a powerful tool for gene function analysis in both N. benthamianaand and wheat at low temperature.